Characteristics and incidence of scabies among pediatric patients at IMCI clinic of caringin primary health center (2022-2023) - Nurlaela, Lutfhi; Rochmah, Elly N; Pradana, Fadhil M; Hidayat, Emma M; Budikusuma, Ludmilla; Indriyana, Sri Q (ACTA Medical Health Sciences, 2025)
Scabies, a parasitic skin infestation caused by Sarcoptes scabiei, primarily affects children under five, presenting with intense pruritus and sleep disturbances. In Bandung City, scabies ranks among the top 21 most commonly reported diseases, with 11,623 cases recorded. Risk factors include poor hygiene practices and suboptimal environmental conditions. This study aimed to characterize the incidence of scabies among children under five treated at the Integrated Management of Childhood Illness (IMCI) Clinic of Caringin Primary Health Center, Bandung City, during 2022–2023. We conducted a descriptive cross-sectional study utilizing secondary data from medical records of diagnosed scabies cases. Analyzed variables included age, gender, nutritional status, and case classification (new or recurrent). Among 196 identified cases (154 in 2022; 42 in 2023), the incidence rate declined from 13.6 to 4.3 per 1,000 children. Most patients were male (57.1%) and aged 2–3 years (49.49%). In terms of nutritional status, 58.67% had normal nutrition, while 21.43% were undernourished, and 17.86% were severely stunted. Recurrent cases predominated in both years, though new cases proportionally increased in 2023. The observed decline in incidence may reflect the efficacy of treatment interventions and preventive programs(e.g., hygiene promotion and sanitation surveillance). However, the the persistent rise in new cases suggest ongoing community transmission. In conclusion, scabies incidence among toddlers attending the IMCI Clinic showed a downward trend during 2022-2023, with highest prevalence in boys aged 2–3 years and normal nutritional status. DOI : 10.35990/amhs.v4n1.p17-25 REFERENCES Romani L, Whitfeld MJ, Koroivueta J, Kama M, Wand H, Tikoduadua L, et al. Mass drug administration for scabies control in a population with endemic disease. New England Journal of Medicine. 2015;373:2305–13. Stephanie AS, Stephanie A. Scabies in the elderly: A narrative literature review. Bioscientia Medicina: Journal of Biomedicine and Translational Research. 2022;6:2377–83. World Health Organization. Scabies. WHO Factsheets. 2023. Ubaidillah. Faktor-faktor yang berhubungan dengan kejadian scabies di Madrasah Tsanawiyah Yogyakarta. Jurnal Kesehatan Kusuma Husada. 2021;89–93. Astanti YOV, Mardiana N, Ardiansyah. Faktor-faktor yang berhubungan dengan kejadian skabies. Jurnal Penelitian Keperawatan. 2025;11:13–22. Akbar KF, Hamsah IA, Darmiati, Mirnawati. Deteksi dini tumbuh kembang balita di posyandu. Jurnal Ilmiah Kesehatan Sandi Husada. 2020;9:2654–63. [Internet]. Available from: https://akper-sandikarsa.e-journal.id/JIKSH Asthiningsih NWW, Wijayanti T. Edukasi personal hygiene pada anak usia dini dengan G3CTPS. Jurnal Untuk Pesut: Pengabdian Kesejahteraan Umat. 2019;1:84–92. Fadlyana E. Pemantauan pertumbuhan anak. Ikatan Dokter Anak Indonesia. 2016. Dinas Kesehatan Kota Bandung. Profil Kesehatan Kota Bandung Tahun 2021. Bandung: Dinas Kesehatan Kota Bandung; 2022. Istiqomah A, Masmur SK, Amali RA, Tiawati S. Peran gizi terhadap pertumbuhan dan perkembangan balita. Antigen: Jurnal Kesehatan Masyarakat dan Ilmu Gizi. 2024;2:67–74. Anggreni PMD, Indira IGAAE. Korelasi faktor predisposisi kejadian skabies pada anak-anak di Desa Songan, Kecamatan Kintamani, Kabupaten Bangli, Provinsi Bali. E-Jurnal Medika. 2019;8. Anwar R. Faktor-faktor yang mempengaruhi status gizi balita di Desa Penggalaman, Kecamatan Martapura Barat. Jurnal Skala Kesehatan. 2022;13. Rosyida IA, Arisandra ML, Noviyanti DA, Aprilian R, Cahyono CB, Abidin KU. Pemantauan status gizi balita dan pentingnya pemberian PMT pada balita di Desa Durikedungjero, Ngimbang, Lamongan. Jurnal Kita Bakti. 2024;5:24–33. Kusuma RM. Antropometri pengukuran status gizi anak usia 24–60 bulan di Kelurahan Bener, Kota Yogyakarta. Jurnal Medika Respati. 2018;13:36–42. Sudirman AA, Ali L. Penerapan manajemen terpadu balita sakit (MTBS) di Puskesmas Kota Gorontalo. Zaitun Jurnal Ilmu Kesehatan. 2015;3. Anggraini R, Yani FF, Rasyid R. Analisis implementasi manajemen terpadu balita sakit (MTBS) terhadap kualitas pelayanan di Puskesmas Kota Padang. JIK Jurnal Ilmu Kesehatan. 2022;6:339–46. Badan Pusat Statistik (BPS) Kota Bandung. Penduduk Kecamatan Babakan Ciparay menurut jenis kelamin dan kelurahan Semester II 2019. Bandung: BPS Kota Bandung; 2020. Setia MS. Methodology series module 3: Cross-sectional studies. Indian Journal of Dermatology. 2016;61. Gunardi KY, Sungkar S, Irawan Y, Widaty S. Level of evidence diagnosis skabies berdasarkan Oxford Centre for Evidence-Based Medicine. eJournal Kedokteran Indonesia. 2022;10:276–83. World Health Organization (WHO). WHO Child Growth Standards: Length/height-for-age, weight-for-age, weight-for-length, weight-for-height and body mass index-for-age: Methods and development. Geneva: WHO Press; 2006. Suryana E, Sopiah M, Agustiawan, Harto S. Early childhood development (physical, intellectual, emotional, social, moral, and religious tasks) implications for education. Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini. 2022;4:362–73. Hervina. Profil kejadian skabies di RSUD Dr. R.M. Djoelham Binjai Sumatera Utara periode Januari 2017–Desember 2021. JUMANTIK (Jurnal Penelitian Kesehatan). 2023;9:30. Yunita MS, Gustia R, Anas E. Faktor-faktor yang berhubungan dengan kejadian skabies di wilayah kerja Puskesmas Lubuk Buaya Kota Padang Tahun 2015. Jurnal Kesehatan Andalas. 2018;7:51–8.